Did Post-Floyd et al. Reforms Reduce Racial Disparities in NYPD Stop, Question, and Frisk Practices? An Exploratory Analysis Using External and Internal Benchmarks. (29th July 2019) - MacDonald, John; Braga, Anthony A.
Abstract : Various methodological approaches to constructing external and internal benchmarks have been applied to estimate racial bias in police stop, question, and frisk (SQF) patterns. We apply an external benchmark of the race of the residential population and an internal benchmark of similarly-situated stops to estimate if racial disparities in New York City SQF data were impacted by the Floyd, et al. v. City of New York court settlement. We find that after the settlement, the racial composition of census tracts were no longer significant predictors of the stop rate after controlling for reported crime, socioeconomic factors, and police precincts. We further find that differences in SQF outcomes and hit rates between Blacks and Hispanics and similarly-situated others diminished substantially after the settlement. These findings suggest that court reforms may be an effective method for reducing racial disparities in SQF patterns.